2020
DOI: 10.47760/ijpsm.2020.v05i12.007
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Pharmacology and Product Development of Lime (Citrus aurantifolia) Rind

Abstract: Lime (Citrus aurantifolia) has many benefits for the human body because it contains several phytochemical compounds, namely alkaloids, flavonoids, steroids, and triterpenoids, saponins, tannins, and phenolics. However, many Indonesian people do not know that not only lime fruit has many benefits; the lime peel also has many benefits for the body. This review provides knowledge about the pharmacological activity and development of pharmaceutical products from the lime peel. The keywords Citrus aurantifolia, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Flavonoid content ranges from 41.38-64.2 µg of QE/mg of methanol dry extract [11]. Flavonoids found in the peel of C. aurantifolia include apigenin, rutin, quercetin, and kaempferol [13]. The distribution of quercetin is slightly different from that of the hesperidin compound, where the highest level of quercetin was found in the fruit peel, which was 112.47 µg/g dry weight, and the lowest level was found in the fruit content, which was 89.4947 µg/g dry weight.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoid content ranges from 41.38-64.2 µg of QE/mg of methanol dry extract [11]. Flavonoids found in the peel of C. aurantifolia include apigenin, rutin, quercetin, and kaempferol [13]. The distribution of quercetin is slightly different from that of the hesperidin compound, where the highest level of quercetin was found in the fruit peel, which was 112.47 µg/g dry weight, and the lowest level was found in the fruit content, which was 89.4947 µg/g dry weight.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Research results from Karatoprak et al (2021) [41] showed that the dry extract of C. aurantifolia fruit using ethanol solvent had the highest total flavonoid content, with a value of 7.83 ± 2.66 mg CA/g extract, when compared to using distilled water and methanol solvent, which produced total flavonoid levels of 6.52 ± 0.77 and 6.27 ± 0.39 mg CA/g extract. The structure of the flavonoids in C. aurantifolia can be seen in Figure 3 [13,70].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Citrus aurantifolia can increase immunity, improve digestion, overcome respiratory tract disorders, reduce the risk of cancer, lose weight, prevent diabetes, and maintain healthy skin. Citrus aurantifolia peel is also used for hand sanitizers, gel products, mosquito repellents, and nanoparticles made of chitosan) (Ramadaini et al 2020) Advokat 'avocado' (Persea americana) fruit contains potassium that is useful for helping control blood pressure and preventing high blood pressure, oral thrush, bladder stones, facilitate menstruation, headaches, asthma, cholesterol, and hypertension. Potassium is also very good to help regulate heart rate to stay normal.…”
Section: Cultural Practices Of Traditional Medicine By Tetun Tribementioning
confidence: 99%
“…Swingle is nutrient-rich and effective as a pesticide, anti-oxidant, anti-bacterial, anti-cancer, and anti-inflammatory agent [9]. These various biological activities are caused by the secondary metabolite content found in lime, namely coumarins, alkaloids, flavonoids [10], limonoids, carotenoids, phenolics, terpenes [11], and essential oils [12]. Every part of lime has benefits, including the peel, which is said to be a good source of pectin, essential oils, and phenolic compounds [13].…”
Section: Introductionmentioning
confidence: 99%